Comrades-in-Arms and Partners in Crime: The German Democratic Republic (GDR) and China in the 1950s and 1960s. (2nd January 2022) - Berkofsky, Axel
Abstract : This article analyzes the quality of selected aspects and issues regarding relations between the German Democratic Republic (GDR) and China in the 1950s and early 1960s. How was Chinese dictator Mao Zedong's Hundred Flowers Campaign perceived and interpreted in East Berlin, and why and until when was GDR leader Walter Ulbricht enthusiastic about Mao's disastrous Great Leap Forward are among the questions this article will seek to answer. As it turned out, East German leaders' assessments and newspaper reporting on Mao's domestic and foreign policy and government propaganda did not in any way correspond with China's on the ground realities. The East German authorities took Chinese propaganda and entirely false statistics and data on steel and agricultural production at face value and ordered its mouthpiece newspapers to do the same. The same was true for Chinese reporting and propaganda on Ulbricht's decision to divide Berlin with a wall in 1961: misleading and nonsensical reporting in support of a fair-weather friendship, which in the wake of the Sino-Soviet Split in the early 1960s would turn into enmity (as ordered by Moscow).